Revised Middle Miocene datum for initial marine flooding of North Croatian Basins (Pannonian Basin System, Central Paratethys) - Ćorić, Stjepan (Array, 2009)
Summary: The Pannonian Basin System (PBS) originated during the Early Miocene as a result of extensional processes between the Alpine-Carpathian and the Dinaride Orogenic Belts. The Paratethys Sea flooded the new basins successively during the Karpatian (late Burdigalian, Early Miocene) and the Early Badenian (middle Langhian, Middle Miocene). The North Croatian Basins (NCB) occupied the south-western margin of the PBS and the Central Paratethys Sea. Their initial marine flooding has until now been dated as Karpatian in age. The transgression into the NCB invaded a lacustrine environment, representing the northern prolongation of the vast Dinaride Lake System extending southwards as far as the Adriatic Plate. We reinvestigate two sections from opposite margins of the NBS – from Mt. Medvednica in the west and from Mt. Požeška in the east, including the corresponding lowermost marine Miocene deposits, in order to critically examine the Karpatian datum. Our new biostratigraphic data, integrating calcareous nannoplankton, planktic and benthic foraminifera, diatom and mollusc records, have substantially revised the previous interpretation. The presence of a calcareous nannoplankton assemblage of the NN5 Zone and the planktic and benthic foraminifera of the regional Lower Lagenidae Zone now place the transgression into the main Early Badenian transgressive pulse of Central Paratethys. Consequently, the initial marine transgression correlates accurately with the middle part of the Early Badenian, which is more than 2 m.y. younger than the previously inferred datum, and at least 1 m.y. younger than the lower boundary of the Badenian and the Middle Miocene, respectively. Finally, the basal lacustrine infill of the NCB, previously dated as Ottnangian (middle Burdigalian, Early Miocene) and continuously grading into marine deposits, has also to be reconsidered as Early Badenian